KREATIVITAS GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI MTs N SUBULUSSALAM - Sabri, Sabri (IAIN Padangsidimpuan, 2019)
The purpose of this study is to find out how the form of teacher creativity in increasing the motivation to learn Islamic religious education of students in MTsN Subulussalam, to find out the factors that are obstacles in developing creativity in increasing motivation to learn Islamic religious education of students in MTsN Subulussalam, to find out the solutions given to obstacles teacher creativity in increasing motivation to learn Islamic Religious Education students at MTsN Subulussalam. Based on the data analysis, this study uses a qualitative approach. This research is descriptive. Data collection instruments used in this study were observation, interviews, and documentation. The respondents in this study were teachers. From the research conducted it was concluded that: 1) the forms of teacher creativity carried out at MTsN Subulussalam are arousing children's motivation and attention, paying attention to differences in children's characteristics, classroom management, repetition, giving gifts, giving praise, holding questions and answers, using teaching aids , singing songs, cheerful teachers, interactions between teachers and students, assignments given by teachers, teachers developing learning resources, competition or competence. 2) Factors that influence the creativity of teachers in increasing student learning motivation are: Student Discipline, Education Level, Facilities, Teachers feel satisfied with the learning carried out. 3) The solution given to the obstacles of teacher creativity in increasing students' motivation to learn Islamic Religious Education is to provide penalties, find boarding houses, teachers work together in creating new creativity, improve facilities, improve the functioning of honest school committees, increase teacher insight by following the program Teacher Subject Meeting.